Integration Of Independent Curriculum Competencies In Craft Learning Content In Junior High School - Rizki Alfiatuzzakiyah; Widiyanti; Didik Nurhadi; Achmadromadin (Didaktika: Jurnal Kependidikan, 2024)
The Independent Curriculum is a curriculum that emphasizes the development of holistic competencies, creativity, and entrepreneurship of students to face the challenges of complex times more effectively. In secondary education, the application of the independent curriculum is able to have a significant impact on learning objectives, including the craft subject on the topic of processing. The research method used is qualitative by applying interview data collection, observation and field documentation studies. The results of the study found that the implementation of the independent curriculum at Nurul Huda Porong Sidoarjo Junior High School was carried out in stages from grade 7, with teachers who had received training to develop their own learning tools. The learning process for food processing crafts is interactive and fun, despite the lack of equipment and practice rooms. The integration of Independent curriculum in food processing craft in junior high schools produces students who are competent and knowledgeable in the culinary world.